Genetic Analysis of Hyperpolarization‐Activated Cyclic Nucleotide‐Gated Cation Channels in Sudden Unexpected Death in Epilepsy Cases - Tu, Emily (Brain Pathol, 2011)
Sudden unexpected death in epilepsy (SUDEP) is the most common epilepsy‐related cause of death, yet the cause is unknown. Our previous studies suggest a role for arrhythmia‐related ion channel genes in the pathogenesis of SUDEP. Hyperpolarization‐activated cyclic nucleotide‐gated cation (HCN1–4) channels are ion channels involved in generating spontaneous rhythmic activity in cardiac pacemaker and neuronal cells. This study sought to determine the role of pathogenic DNA variants in the HCN1–4 genes in a large SUDEP cohort collected from 1993 to 2009. Post‐mortem DNA samples were amplified and analyzed for each HCN exon. Genetic analysis in 48 SUDEP cases (age range 12–82 years) identified six novel and three previously reported nonsynonymous (amino acid changing) variants in HCN1 (n = 1), HCN2 (n = 2), HCN3 (n = 2) and HCN4 (n = 4). The Phe738Cys and Pro802Ser variants in HCN2, and Gly973Arg in HCN4 were absent in control alleles and affecting highly conserved residues in the carboxyl‐cytoplasmic tail region. Our results support a pathogenic link between the heart and brain in SUDEP, mediated by the HCN neuro‐cardiac ion channel genes.